2022
DOI: 10.3390/brainsci12111473
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy—A Neuropathological Obscure Sleep Disorder: A Narrative Review of Current Literature

Abstract: Narcolepsy is a chronic, long-term neurological disorder characterized by a decreased ability to regulate sleep–wake cycles. Some clinical symptoms enter into differential diagnosis with other neurological diseases. Excessive daytime sleepiness and brief involuntary sleep episodes are the main clinical symptoms. The majority of people with narcolepsy experience cataplexy, which is a loss of muscle tone. Many people experience neurological complications such as sleep cycle disruption, hallucinations or sleep pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 202 publications
0
5
0
2
Order By: Relevance
“…Many people experience neurological complications such as sleep cycle disruption, hallucinations, or sleep paralysis. Because of the associated neurological conditions, the exact pathophysiology of narcolepsy is unknown (6).…”
Section: Some Clinical Symptoms Enter Into Differential Diagnosis Wit...mentioning
confidence: 99%
“…Many people experience neurological complications such as sleep cycle disruption, hallucinations, or sleep paralysis. Because of the associated neurological conditions, the exact pathophysiology of narcolepsy is unknown (6).…”
Section: Some Clinical Symptoms Enter Into Differential Diagnosis Wit...mentioning
confidence: 99%
“…A sejtpusztulás hátterében genetikai és környezeti faktorok jelenlétét feltételezik. Elsőfokú rokonok között a narcolepsia kialakulásának esélye 10-40-szer nagyobb, mint az átlagpopulációban [13], sporadikus formákban. A jellegzetes HLA-konfiguráció is aláhúzza a genetikai fogékonyságot.…”
Section: A Narcolepsia Patofiziológiájaunclassified
“…Megjegyzendő, hogy protektív alléleket is azonosítottak (HLA-DQB1 06:03, 05:01). A környezeti faktorok szerepét jelzi, hogy egypetéjű ikreknél csak az esetek 25-31%-ában van jelen mindkettőjüknél a betegség [13].…”
Section: A Narcolepsia Patofiziológiájaunclassified
“…However, its illicit use and recreational consumption have become significant concerns in many countries. Despite its therapeutic applications in conditions like memory disorders, hyperactivity, narcolepsy, and obesity, it is being used illegally as a recreational drug (10)(11)(12). Research has indicated that this substance can have side effects on the respiratory, cardiovascular, and nervous systems (13,14).…”
Section: Introductionmentioning
confidence: 99%